Pasteurization of blackberry juice preserves polyphenol-dependent inhibition for lipid peroxidation and intracellular radicals - Azofeifa Cordero, Gabriela (2015)
Berries are commonly consumed as juice, and juice-processing conditions could affect their bioactive compounds. This study evaluated the effect of thermal treatments on the antioxidant capacity of blackberry juice polyphenols. Pasteurized blackberry juices were prepared at 75 °C for 15 s (JP75) and 92 °C for 10 s (JP92). Polyphenol analysis showed that for JP75 and JP92, anthocyanin concentrations decreased significantly, compared to non-pasteurized juice (NPJ), whereas ellagitannins were not significantly affected. The evaluation of the DPPH (2,2-diphenyl-1-picrylhydrazyl) scavenging capacity showed a significant decrease of 26% for JP75 and 27% for JP92, and, for the NO (nitric oxygen) scavenging capacity, the activity was reduced 15% for JP75 and 16% for JP92. There were no significant reductions observed for the peroxidation inhibitory capacity of the pasteurized juices for any of the oxidation substrates tested: liposomes, liver homogenates and erythrocytes. Furthermore, the intracellular antioxidant capacity showed no significant differences due to thermal treatments. The concentration of phenols necessary to scavenge 50% of the radical oxygen species was 204 ± 9 μg/mL for NPJ, 219 ± 10 μg/mL for JP75 and 220 ± 9 μg/mL for JP92. This study revealed that pasteurized blackberry juices maintained their biological properties related to inhibition of peroxidation and their capacity to scavenge intracellular radicals.